Crop water productivity of irrigated teff in a water stressed region - Yihun, Y.M.; Haile, A.M.; Schultz, B.; Erkossa, Teklu (Springer, 2013)
In water stressed regions such as the Central Rift Valley of Ethiopia, increasing Crop Water Productivity (CWP) is imperative for sustainable food and water security. This paper presents CWP of Teff (Eragrostic Tef), a staple food in Ethiopia and an important export crop. Field experiments were conducted under irrigated agriculture during the dry seasons in the periods: 1) November 2010 to March 2011; and 2) December 2011 to April, 2012 at Melkassa Agricultural Research Centre in Ethiopia. Teff crop was irrigated at sixteen different water application depths ranging from 100 to 25 % of the optimum Crop Water Evapotranspiration (ETc.) during the four growing stages, the initial, development, mid season and late season. The effect of seeding rates of 25 kg/ha and 10 kg/ha on lodging and yield of the crop was also determined. The main results were: 1) At 25 % deficit irrigation applied for the whole growth period, Teff CWP was the highest at 1.16 and 1.08 kg/m3 respectively for the seeding rates of 25 kg/ha and 10 kg/ha; 2) the CWP slightly decreased to 1.12 and 1.07 kg/m3 when the 25 % deficit was applied during the late season stage; 3) the crop yield response factor (Ky) of 1.09 and 1.19 was obtained for seeding rates of 25 kg/ha and 10 kg/ha respectively; the equivalent biomass response factor (Ky) was less at 0.88 and 0.96 respectively.